PENERAPAN MODEL PEMBELAJARAN DISCOVERY DENGAN MEDIA KONKRET DALAM PENINGKATAN HASIL BELAJAR IPA TENTANG SIFAT-SIFAT CAHAYA PADA SISWA KELAS V SD NEGERI KALIPUTIH TAHUN AJARAHN 2016/2017 - Permatasari, Nurul Dwi; Suyanto, Imam; Rokhmaniyah, Rokhmaniyah (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: THE USE OF DISCOVERY LEARNING MODEL WITH CONCRETE MEDIA IN ENHANCEMENT OF LEARNING RESULTS ABOUT LIFE PROPERTIES IN STUDENT CLASS V SD NEGERI KALIPUTIH IN THE ACADEMIC YEAR OF 2016/2017. The objectives of this research are: (1) to describe the steps of learning discovery model with concrete media; (2) improving science learning outcomes about the properties of light; (3) to describe the constraints and solutions of using discovery learning model with concrete media in improving science learning outcomes about light properties. This study uses collaborative classroom action research. The subjects of this study are the students of class V which amounted to 20 students. Data collection techniques used: observation, interviews, and tests. Data validity was using source triangulation and engineering triangulation. Data analysis is using data reduction, data presentation, and conclusion. The results showed that the application of discovery learning model with concrete media can improve science learning result about light properties.Keywords: Discovery, concrete media, science learning outcomes